Fyn and argonaute 2 participate in maternal-mRNA degradation during mouse oocyte maturation. Issue 8 (18th April 2022) - Gindi, Natalie; Grossman, Hadas; Bar-Joseph, Hadas; Miller, Irit; Nemerovsky, Luba; Hadas, Ron; Nevo, Nava; Galiani, Dalia; Dekel, Nava; Shalgi, Ruth
ABSTRACT: Fertilization triggers physiological degradation of maternal-mRNAs, which are then replaced by embryonic transcripts. Ample evidence suggests that Argonaut 2 (AGO2) is a possible post-fertilization regulator of maternal-mRNAs degradation; but its role in degradation of maternal-mRNAs during oocyte maturation remains obscure. Fyn, a member of the Src family kinases (SFKs), and an essential factor in oocyte maturation, was reported to inhibit AGO2 activity in oligodendrocytes. Our aim was to examine the role of Fyn and AGO2 in degradation of maternal-mRNAs during oocyte maturation by either suppressing their activity with SU6656 – an SFKs inhibitor; or by microinjecting DN-Fyn RNA for suppression of Fyn and BCl-137 for suppression of AGO2. Batches of fifteen mouse oocytes or embryos were analyzed by qPCR to measure the expression level of nine maternal-mRNAs that were selected for their known role in oocyte growth, maturation and early embryogenesis. We found that Fyn/SFKs are involved in maintaining the stability of at least four pre-transcribed mRNAs in oocytes at the germinal vesicle (GV) stage, whereas AGO2 had no role at this stage. During in-vivo oocyte maturation, eight maternal-mRNAs were significantly degraded. Inhibition of AGO2 prevented the degreadation of at least five maternal-mRNAs, whereas inhibition of Fyn/SFK prevented degradation of at least five Fyn maternal-mRNAs and two SFKs maternal-mRNAs; pointing at their role in promoting the physiological degradation which occurs during in-vivo oocyte maturation. Our findings imply the involvement of Fyn/SFKs in stabilization of maternal-mRNA at the GV stage and the involvement of Fyn, SFKs and AGO2 in degradation of maternal mRNAs during oocyte maturation.